ANALISIS HUBUNGAN KINERJA SISTEM INFORMASI AKADEMIK KEMAHASISWAAN, DITINJAU DARI SEGI KEAMANAN INFORMASI, TERHADAP KEPUASAN MAHASISWA: STUDI KASUS PADA FAKULTAS ILMU KOMPUTER UNIVERSITAS INDONESIA - Irawan Irawan (Universitas Budi Luhur, 2013)
This research is aimed to measure the students’ satisfaction of SIAK-NG. SIAK-NG is an information system to facilitate the students in Universitas Indonesia to plan the students’ studies. This is a Quantitative Research. Meanwhile the question of this research is do the students’ satisfy to the information security in SIAK-NG. The students’ satisfaction will effect to the quality of this University. Primary data was taken from the field survey by spreading the questionnaire to the sample which are selected. The researcher use Ramdom sampling in choosing the samples because it deals directly with the system. Secondary data obtained from various sources, both within the institution and outside the institution as well as books and records relating to the problem under study. The data obtained will be used for the descriptive data analysis with statistical methods. The test results and analysis are expected to provide results on the allegation the influence of variables on student satisfaction information security.Keyword: Next-Generation Student Academic Information Systems (SIAK-NG), Information Security, Student Satisfaction.